Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/anzf.1103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cultural Issues for Constellation Work in South Africa

Abstract: Constellation work is a therapeutic and counselling intervention recognised in Germany and other European countries since the 1970s. Various scientists and practitioners have contributed to its theoretical and practical development, and research on the subject has increased over the past few years. However culture in constellation work has received little research attention and has not been empirically studied in African contexts. The aim of this article is to reflect on culture and its influence on constellat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Bakker and Snyders (1999) have argued that while the core principles of family therapy may be consistent with African settings, blind adoption of a Western-family model to problem-solving is problematic as it ignores the larger socioeconomic, religious, historical, and political contexts. Mayer and Viviers (2015) demonstrate that consideration of such contextual issues, through approaches to family therapy such as Family Constellation Work, results in positive experiences for clients. While the involvement of family members may enhance client investment in the therapeutic relationship and drive client retention and progress, more research needs to be done to identify when family involvement in Ghanaian settings is appropriate and when it is contraindicated.…”
Section: Discussionmentioning
confidence: 95%
“…Bakker and Snyders (1999) have argued that while the core principles of family therapy may be consistent with African settings, blind adoption of a Western-family model to problem-solving is problematic as it ignores the larger socioeconomic, religious, historical, and political contexts. Mayer and Viviers (2015) demonstrate that consideration of such contextual issues, through approaches to family therapy such as Family Constellation Work, results in positive experiences for clients. While the involvement of family members may enhance client investment in the therapeutic relationship and drive client retention and progress, more research needs to be done to identify when family involvement in Ghanaian settings is appropriate and when it is contraindicated.…”
Section: Discussionmentioning
confidence: 95%
“…The method has gained popularity not only in Europe (Hrncic, 2017;Hunger et al, 2014;Stiefel et al, 2002) but also in the United States (Cohen, 2006;Hellinger, 2003b;Mayer & Viviers, 2016;Stones, 2006), China, Mexico, South Africa, and Australia (Duncan, 2017;Mayer & Viviers, 2015Pritzker & Duncan, 2019).…”
Section: The Emergence Of Family Constellation Therapymentioning
confidence: 99%
“…During the last decades, several conferences and hundreds of workshops have been held on family constellation in Germany, the Netherlands, Spain, Hungary, and the United Kingdom (Stones, 2006; Zseni et al, 2011). The method has gained popularity not only in Europe (Hrncic, 2017; Hunger et al, 2014; Stiefel et al, 2002) but also in the United States (Cohen, 2006; Hellinger, 2003b; Mayer & Viviers, 2016; Stones, 2006), China, Mexico, South Africa, and Australia (Duncan, 2017; Mayer & Viviers, 2015, 2016; Pritzker & Duncan, 2019).…”
Section: The Emergence Of Family Constellation Therapymentioning
confidence: 99%
“…Within the South African society, indigenous healing is en vogue (Mpofu, Peltzer, & Bojuwoye, 2011), and numerous South Africans consult traditional healers (Ross, 2007) and use natural substances, prayer, and various rituals to support mental and physical well-being. Research shows that for medical and psychological healing, constellation work (CW) is used in different societies and cultural groups (Mason Boring, 2004; Van Kampenhout, 2003, 2008); however, hardly any study can be found on CW in South African contexts (Mayer & Viviers, in press). At the same time, psychological discourses aim at combining traditional and psychological healing and therapies (Moodley & West, 2005) for developing mental health and well-being (Berg, 2003).…”
Section: Introductionmentioning
confidence: 99%